Analysis Of Leg Muscle Explosive Power and Foot Coordination on Shooting Skills in The SSB Bontongan Club in Enrekang District - Irvan, Irvan; Muhammadong, Muhammadong; Hudain, Muh. Adnan; Rusli, Rusli; Nuralam, Nuralam (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objectives. The objective of this research was to determine the effect of leg explosive power and ankle coordination on shooting skills in soccer games at the SSB Bontongan Club in Enrekang Regency Materials and Methods. The population is all athletes from the SSB Bontongan Club, Enrekang Regency with the number of samples used being 25 athletes with the sampling technique being the total population. The data analysis techniques used are descriptive analysis, data normality test, linearity test, categorization analysis and regression analysis using the SPSS 20.00 program at a significance level of 95% or α 0.05. Results. The results of the research show that leg muscle explosive power and ankle coordination have a significant effect on shooting skills in soccer games at the SSB Bontongan Club in Enrekang Regency by 84.4%. Conclusions. Based on the research results and discussions that have been presented, the following conclusions can be drawn: 1) There is a contribution of leg muscle explosive power on shooting skills in soccer games at the SSB Bontongan Club in Enrekang Regency, 2) There is a contribution of eye-foot coordination on shooting skills in soccer games at the SSB Bontongan Club in the Regency, and 3) There is a contribution of leg explosive power and ankle coordination together on shooting skills in soccer games at the SSB Bontongan Club in Enrekang Regency.